Revolutionizing Education: The Islamic Perspective on Merdeka Belajar Curriculum and its Successful Implementation at a Middle School in East Kalimantan - Hasanuddin Hasanuddin; Umar Fauzan; Noor Malihah (STAI Hubbulwathan Duri, 2023)
This research aims to discuss the revolutionizing Education in Indonesia that shows the problem in campaigning for the Merdeka Belajar curriculum because the curriculum always develops and keeps up with the times. Updating the curriculum is essential to provide students with an education that meets future needs. As well as teachers at MTs Negeri East Kalimantan follow the Ministry of Education and Culture policy, whereas the Ministry of Religion adapts according to the learning needs of the madrasah to strengthen Islamic Religious Education, which is its characteristics. The data analysis technique uses a single data analysis method based on phenomena by Larkin and Thompson (Interpretative Phenomenological Analysis) and comparative analysis techniques by Chris Ryan (Cross-Case Analysis). Besides that, the data validity test used Norman K. Denzin's theory in three stages: data source, theory, and method triangulation. The results show that the conception of Merdeka Belajar from an Islamic perspective puts forward Holistic Islamic Education, the values of freedom of thought, independence, and teacher responsibility in innovating. While implementing the Merdeka Belajar curriculum will support teachers to value students who have the right to pass or not through the educational transformation without national exams; students will explore various aspects of themselves through the madrasah assessment and give freedom to schools in designing and implementing curricula through more efficient lesson plans.